(3JaQjO GdLRGA GdLfGFj aj bGfhf GdYbhHGJ GdCQOfj (B: s (3OQGSI ebGQfI (B/ s - (3LdGd MSjf MeOGf GdcGjOs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3ef GdeYdhe Cf JaQjO GdLRGA GdLfGFj XgQ bOjkeG efP fTCI GdbhGfjf GdhVYjI hef bHdgG GdTQjYI GdESdGejI abO XgQ HeSejGJ eJYOOI(B: (3hJWhQ eY JWhQ GdHTQjI hGdLQGFe(B: (3acGf dg CcHQ GdCKQ aj JMbjb GdfJjLI GdeQLhI ef EjbGY GdYbhHI Ydi GdLGfj(B: (3hgj EUdGMg hEYGOI OeLg eY GdeLJeY(B: (3hMeGjI eUGdM GdeLJeY hGdeUdMI GdYGeI(B: (3aaj hbJfG GdMGVQ JJUOi ddJaQjO GdLfGFj YOI LgGJ efP HOGjI hVY GdJTQjY GdLfGFj(B: (3ajJUOi dg GdeTQY GHJOGkA(B: (3MjK jVY GdLQjeI hGdYbhHI YdjgG Ydi Tcd fU LfGFj hjJQc ddbGVj MQjI GdGNJjGQ Hjf MOjf CYdi hCOfi hjSei Pdc HGdJaQjO GdJTQjYj(B: (3Ke jCJj OhQ GdbGVj ddGNJjGQ Hjf gPjf GdMOjf MSH XQha GdLQjeI hGdeLQe(B: (3hjSei Pdc HGdJaQjO GdbVGFj(B: (3Ke jCJj OhQ GdLgI GdJfajPjI ddYbGH hGdJj JJhdi JfajP GdYbhHI GdeMche HgG Ydi GdLGfj hGdJj dgG JbUjQ eOI GdYbhHI EPG QCJ CfgG MbbJ GdfJjLI GdeQLhI efgG Edi MO eYjf HGdbGfhf GdLfGFj s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B296-329s
Keywords: (3JaQjO GdLRGA GdLfGFjs; (3GdJaQjO GdJTQjYj s; (3GdJaQjO GdLRGFj s; (3TQYjI GdYbhHI GdLfGFjIs; (3eHOG GdTQYjI GdLfGFjIs; (3GdJOGHjQ GdGMJQGRjIs; (3GdJaQjO GdbVGFj s; (3GdJaQjO GdJfajPjs; (3GdeYGedI GdYbGHjI ddGMOGKs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs